PROSES HUKUM BAGI PELAKU YANG MENGALAMI GANGGUAN KEJIWAAN BERDASARKAN PASAL 44 KITAB UNDANG UNDANG HUKUM PIDANA - Sinaga, Bob Steven; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
People who have a psychiatric disorder should not be convicted, but bring them to a mental hospital. People who experience mental illness common in our country Indonesia, this is influenced by the economic situation, families brokemhom, as well as the pain that comes from an innate, so many patients who have psychiatric disorders escaped from a mental hospital and follow- pidana.Dalam the investigation process there are problems on the hard evidence against the perpetrators of people who experience mental illness committing criminal offenses so that offenders are already undergoing treatment in a mental hospital and is considered to have legal protection under article 44 KUH. Objectives achieved in this study to determine how the investigation process against the perpetrators of criminal acts who have psychiatric disorders based on Article 44 of the Penal Code and how the criminal responsibility of the perpetrators of criminal acts who experience mental illness.This type of research can be classified in this type of normative juridical research, because this research author discusses the legal principles, systematic law, the degree of synchronization of law, legal history and comparative law and in order to give a complete picture and clear about the issues examined by the author. This research was conducted with normative method, the data source used by the cases on the internet and study of literatureFrom the research problem there are two main things that can be inferred First, how the process of the investigation of the criminal mentally challenged under section 44 Criminal Code, that in the process of investigation in charge of the investigation is a special investigator in encountering cases of investigation of people who experience mental illness already never entered into a mental hospital why the police are still conducting an investigation and did not dismiss the investigation and could acquire the evidence. Both how the criminal responsibility of the perpetrators of criminal acts who experience mental illness, that is written in the Law of Penal known criminal eraser reasons that justify and excuses as defined excuses that reason remove errors from sipelaku an offense.Keywords: Process punishment Crime-Mental Disorders